Soil fauna communities and microbial activities response to litter and soil properties under degraded and restored forests of Hyrcania - Bazyari M; Etemad V; Kooch Y; Shirvany A (iForest - Biogeosciences and Forestry, 2021)
Reforestation has long been the best practice to restore degraded forests due to human interventions. In this paper we investigated the effect of forest degradation (DNF) along with reforestation using 4 endemic species (Alnus subcordata, ASP; Acer velutinum, AVP; Cupressus sempervirens, CSP; Quercus castaneifolia Mey, QCP) on forest’s soil chemical and biological indicators compared to a close-to-virgin natural forest (VNF). For this study, a total of 24 physico-chemical and 25 biological and microbial indicators were measured in soils of all 6 forest stands along with the litter properties. Results showed that the lowest soil quality was observed under DNF, CSP, and QCP which was the result of forest cover degradation in DNF and low litter quality, especially low pH and high C:N, in CSP and QCP. Soil fauna communities were significantly affected by tree species. We found two times higher density of earthworms in VNF compared to ASP, but in DNF the density was 5 times lower than VNF. We found no epigeic earthworms in QCP, CSP and DNF and no endogeic earthworms in DNF. Acarina and Collembola density was high in VNF and ASP, but they showed significant differences (VNF>ASP), and their density sharply decreased in other stands, especially in CSP (3 times lower than VNF) and DNF (8 to 10 times lower than VNF). Nematode density was statistically equal in VNF, ASP, and AVP, but significantly lower in other stands. Protozoa, bacteria and fungi densities were significantly higher in VNF and ASP (VNF>ASP) compared to each other and other forest stands. Basal respiration, substrate induced respiration, microbial biomass N and P, and carbon availability index was also higher in VNF and ASP compared to other stands. Although VNF has the best condition because of old forest cover and high diversity, ASP soil showed significant improvements, demonstrating the importance of litter quality in soil restoration. Restoration effectiveness ranking of the four tested species on soil improvement are therefore ASP>AVP>QCP>CSP. The significant improvement of soil quality under ASP compared to other reforestated stands, only after 3 decades, emphasizes the importance of tree species selection and litter quality on soil chemical and biological restoration.